The Monetary Policy in the System of State Regulation of the Indian Economy - N. V. Galistcheva (Vestnik MGIMO-Universiteta)
The main task of this research is the analysis of India's monetary policy and its place in the system of state regulation of the economy. The article highlights the main directions of the Indian monetary policy in 1990-2000s aiming to raise competitiveness of the Indian goods on the foreign markets as well as stimulating the inflow of foreign capital in necessary volumes into the national economy. The author focuses on the main instruments of the modern Indian monetary policy, pursued in line with providing the undervalued rupee, which include the manipulating of the bank rate and currency interventions, directed mainly at sterilization of excessive inflow of foreign currency to the country. The article also underlines all the advantages and costs of the monetary policy. One of its main advantages is stimulation of national production's exports and among costs there are difficulties of importing machines and equipment into the country, increase of inflation rate as a result of massive inflow of export revenue, difficulties at external debt's service. The author notes the gradual nature of introduction of current account rupee convertibility and reasons for delay in achieving its full convertibility. Among them there are rather high level of fiscal deficit of the consolidated budget, essential average annual level of inflation, problems of non-performed assets in the economy, high liquidity ratio for commercial banks. The article also presents statistical data on the present state of the Indian foreign exchange reserves as well as dynamics in nominal and real effective exchange rate of rupee in 2005/06 - 2013/14 fiscal year.